Second-Order Nonlinear Optical Microscopy of a H–Si(111)1 × 1 Surface in Ultra-High Vacuum Conditions. (11th April 2012) - Miyauchi, Yoshihiro
Abstract : This paper reviews the use of optical sum frequency generation (SFG) and second harmonic generation (SHG) microscopy under ultra-high vacuum (UHV) conditions to observe the dynamics of a hydrogen terminated Si(111)1 × 1 surface. First, we took SFG and SHG microscopic images of the surface after IR light pulse irradiation and found that the SHG and nonresonant SFG signals were enhanced, probably due to the formation of dangling bonds after hydrogen desorption. Second, we observed time-resolved SFG intensity images of a H–Si(111)1 × 1 surface. After visible pump light irradiation, the nonresonant SFG signal increased at probe delay time 0 ps and then decreased over a life time of 565 ps. The resonant SFG signal reduced dramatically at 0 ps and then recovered with an anisotropic line shape over a life time of 305 ps. The areas of modulated SFG signals at delay time 277 ps were expanded with an anisotropic aspect. Finally, we observed SFG intensity images of hydrogen deficiency on a Si(111)1 × 1 surface as a function of temperature. These images of the H–Si(111) surface, taken with a spatial resolution of 5 μ m at several temperatures from 572 to 744 K, showed that the hydrogen desorbs homogeneously.